Desiring divinity self-deification in early Jewish and Christian mythmaking - Litwa, M. David 1982- (New York, NY Oxford University Press, 2016)
Perhaps no declaration incites more outrage than a human's claim to be God. Those who make this claim in ancient Jewish and Christian mythology are typically either demonized or deified. This work examines this topic
Includes bibliographical references and index
Previously issued in print: 2016
Zielgruppe - Audience: Specialized
Keywords: God; Deification (Christianity); Apotheosis; Judaism -- Doctrines; Judaism ; Doctrines